Categorical confusions: gender and the colonial construction of the ‘Chinese Buddhist’ in Burma - Venker, Matthew (Legal Pluralism and Critical Social Analysis, 2023)
British law in colonial Burma separated the legal personhood of imperial subjects by religious status. However, colonial law failed to clarify boundaries around religious categories. This lack of clarity was amplified when the court was forced to consider how to apply Buddhist law between different Buddhist communities, like the Chinese and Burmese. Owing to differences in how marriage, divorce, succession, and other rights are handled in Chinese- versus Burmese legal traditions, recognition as either Chinese or Burmese carried significant weight. Through a historical anthropology of Chinese-Burmese Buddhist family law in colonial Burma, this article argues that the British colonial judiciary’s failure to appreciate connections between Burmese and Chinese Buddhists produced novel legal segregations of mixed communities. Further, this categorical splitting was generated along gendered lines, where judicial acceptance of men’s claims of Chinese separateness disenfranchised native, mixed, and migrant women who sought to foreground their connections to Burma.